2004
DOI: 10.2134/agronj2004.5380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilization Rate, Stockpiling Initiation Date, and Harvest Date on Canopy Height and Dry Matter Yield of Autumn‐Stockpiled Bermudagrass

Abstract: ter. Recently, there has been increased interest in the utilization of autumn-stockpiled standing bermudagrass Autumn stockpiling is a management technique in which forage for this purpose (Lalman et al., 2000; Scarbrough et al., is allowed to accumulate throughout the late summer and early fall 2001). Stockpiled forages can provide winter pasture for for subsequent grazing throughout the late fall and winter. Wellgrazing livestock, thereby reducing the need for suppleestablished stands of common and 'Tifton 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
2
6
0
Order By: Relevance
“…The values in this study were comparable to those of Scarbrough et al. (2004) who reported DM yield for stockpiled bermudagrass ranging from 924 to 2,254 lb/acre. Fike et al.…”
Section: Forage Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…The values in this study were comparable to those of Scarbrough et al. (2004) who reported DM yield for stockpiled bermudagrass ranging from 924 to 2,254 lb/acre. Fike et al.…”
Section: Forage Yieldsupporting
confidence: 90%
“…Bermudagrass is extremely responsive to N fertilization, and herbage yield increases with N application (Ball et al, 2015). The values in this study were comparable to those of Scarbrough et al (2004) who reported DM yield for stockpiled bermudagrass ranging from 924 to 2,254 lb/acre. Fike et al 2017reported that PGPR-treated bermudagrass hay was similar to hay treated with 25 lb N/acre.…”
Section: Forage Yieldsupporting
confidence: 88%
“…Nitrogen application date did not affect fall forage accumulation ( Table 2). The date when stockpiling began was likely more important to forage accumulation than N application date (6). In southern Oklahoma, initiation of stockpiling in early August and application of N fertilizer by 15 October would enable forage to accumulate before a killing frost, provided rainfall is sufficient to support growth during this period.…”
Section: Nitrogen Fertilizer Rate and Application Date Effectsmentioning
confidence: 99%
“…Poore et al (2000) confirmed that one of the main factors influencing the yield and nutritive value of stockpiled tall fescue was N fertilization. The fact that dry matter (DM) yields increase with increasing N rates on stockpiled tall fescue is well known (Collins & Balasko, 1981a;Gerrish et al, 1994;Kallenbach et al, 2017;Riesterer et al, 2000;Scarbrough et al, 2004;Teutsch et al, 2011;Teutsch et al, 2005). Tall fescue yield in Kentucky was over two-fold higher (1,822 vs 3,843 kg DM ha −1 ) when 100 kg N ha −1 as ammonium nitrate (AN) was applied in mid-August and the forage harvested in early November (Taylor & Templeton, 1976).…”
Section: Introductionmentioning
confidence: 99%